Reactions to Multiple Ascending Doses of the Microtubule Stabilizer TPI-287 in Patients With Alzheimer Disease, Progressive Supranuclear Palsy, and Corticobasal Syndrome: A Randomized Clinical Trial - Tsai, Richard M; Miller, Zachary; Koestler, Mary; Rojas, Julio C; Ljubenkov, Peter A; Rosen, Howard J; Rabinovici, Gil D; Fagan, Anne M; Cobigo, Yann; Brown, Jesse A; Jung, Joo In; Hare, Emma; et al. (Archives of neurology (Chicago), 2020)
Basket-design clinical trials that allow investigation of treatment effects on different clinical syndromes that share the same molecular pathophysiology have not previously been attempted in neurodegenerative disease. To assess the safety, tolerability, and pharmacodynamics of the microtubule stabilizer TPI-287 (abeotaxane) in Alzheimer disease (AD) or the 4-repeat tauopathies (4RT) progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS). Two parallel-design, double-blind, placebo-controlled phase 1 randomized clinical trials in AD and 4RT were conducted from December 20, 2013, through May 4, 2017, at the University of California, San Francisco, and University of Alabama at Birmingham. A total of 94 patients with clinically diagnosed AD (n = 39) and 4RT (n = 55) were screened; of these, 3 refused to participate, and 10 with AD and 11 with 4RT did not meet inclusion criteria. A total of 29 patients with AD, 14 with PSP, and 30 with β-amyloid-negative CBS (determined on positron emission tomography findings) were enrolled. Data were analyzed from December 20, 2013, through May 4, 2017, based on modified intention to treat. Randomization was 8:3 drug to placebo in 3 sequential dose cohorts receiving 2.0, 6.3, or 20.0 mg/m2 of intravenous TPI-287 once every 3 weeks for 9 weeks, with an optional 6-week open-label extension. Primary end points were safety and tolerability (maximal tolerated dose) of TPI-287. Secondary and exploratory end points included TPI-287 levels in cerebrospinal fluid (CSF) and changes on biomarker, clinical, and neuropsychology measures. A total of 68 participants (38 men [56%]; median age, 65 [range, 50-85] years) were included in the modified intention-to-treat analysis, of whom 26 had AD (14 women [54%]; median age, 63 [range, 50-76] years), and 42 had 4RT (16 women [38%]; median age, 69 [range, 54-83] years). Three severe anaphylactoid reactions occurred in TPI-287-treated patients with AD, whereas none were seen in patients with 4RT, leading to a maximal tolerated dose of 6.3 mg/m2 for AD and 20.0 mg/m2 for 4RT. More falls (3 in the placebo group vs 11 in the TPI-287 group) and a dose-related worsening of dementia symptoms (mean [SD] in the CDR plus NACC FTLD-SB [Clinical Dementia Rating scale sum of boxes with frontotemporal dementia measures], 0.5 [1.8] in the placebo group vs 0.7 [1.6] in the TPI-287 group; median difference, 1.5 [95% CI, 0-2.5]; P = .03) were seen in patients with 4RT. Despite undetectable TPI-287 levels in CSF, CSF biomarkers demonstrated decreased chitinase-3-like protein-1 (YKL-40) levels in the 4RT treatment arm (mean [SD], -8.4 [26.0] ng/mL) compared with placebo (mean [SD], 10.4 [42.3] ng/mL; median difference, -14.6 [95% CI, -30.0 to 0.2] ng/mL; P = .048, Mann-Whitney test). In this randomized clinical trial, TPI-287 was less tolerated in patients with AD than in those with 4RT owing to the presence of anaphylactoid reactions. The ability to reveal different tau therapeutic effects in various tauopathy syndromes suggests that basket trials are a valuable approach to tau therapeutic early clinical development. ClinicalTrials.gov identifiers: NCT019666666 and NCT02133846.